2010
DOI: 10.5194/nhess-10-121-2010
|View full text |Cite
|
Sign up to set email alerts
|

Water vapour distribution at urban scale using high-resolution numerical weather model and spaceborne SAR interferometric data

Abstract: Abstract. The local distribution of water vapour in the urban area of Rome has been studied using both a high resolution mesoscale model (MM5) and Earth Remote Sensing-1 (ERS-1) satellite radar data. Interferometric Synthetic Aperture Radar (InSAR) techniques, after the removal of all other geometric effects, estimate excess path length variation between two different SAR acquisitions (Atmospheric Phase Screen: APS). APS are strictly related to the variations of the water vapour content along the radar line of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…3118 F. Alshawaf et al: Estimating trends in atmospheric water vapor and temperature time series based estimates of zenith total delay (ZTD) or PWV have been assimilated into numerical weather prediction models to improve the quality of the output (Bock et al, 2005;Bennitt and Jupp, 2012). They have also been used to improve the performance of high-resolution atmospheric models (Pichelli et al, 2010). Besides meteorology, GNSS estimates of PWV have been employed over Scandinavia for climatological research (Elgered and Jarlemark, 1998;Gradinarsky et al, 2002;Nilsson and Elgered, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…3118 F. Alshawaf et al: Estimating trends in atmospheric water vapor and temperature time series based estimates of zenith total delay (ZTD) or PWV have been assimilated into numerical weather prediction models to improve the quality of the output (Bock et al, 2005;Bennitt and Jupp, 2012). They have also been used to improve the performance of high-resolution atmospheric models (Pichelli et al, 2010). Besides meteorology, GNSS estimates of PWV have been employed over Scandinavia for climatological research (Elgered and Jarlemark, 1998;Gradinarsky et al, 2002;Nilsson and Elgered, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Fiori et al (2009) investigated how the uncertainty in the numerical weather prediction of severe weather events could be affected by increasing the model grid resolution and by choosing a parameterization which is able to represent turbulent processes at such finer scales. Pichelli et al (2010) investigated the ability of high resolution meso-scale model (MM5, see Tremback, 1990) in reconstructing high resolution water vapor fields over the urban area of Rome, Italy, and its surroundings. Results showed that the high resolution Integrated Water Vapour model maps are in good agreement with the Interferometric Synthetic Aperture Radar ones.…”
Section: Modeling Studiesmentioning
confidence: 99%
“…The influence of water vapor in the observations can be reduced by averaging a large number of interferograms (Zebker et al, 1997) or by time series analysis that indicates the stable persistent scatterers (Ferretti et al, 2001;Hooper et al, 2007). Besides, InSAR has recently been used to derive the phase shift caused due to the propagation in the Earth's atmosphere from the interferograms or by time series analysis (Hanssen, 2001;Meyer et al, 2008;Pichelli et al, 2010;Alshawaf et al, 2012). Global Navigation Satellite Systems (GNSS), however, have been considered since the 1990s as an efficient microwave-based tool for atmospheric sounding (Bevis et al, 1992;Rocken et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Numerical atmospheric prediction models are increasingly used to provide simulations of the atmospheric parameters. Various studies suggested the assimilation of atmospheric parameters, such as water vapor, estimated from the Global Positioning System (GPS) or Interferometric Synthetic Aperture Radar (InSAR), into these models to improve the quality of the simulated parameters (Pichelli et al, 2010;Bennitt and Jupp, 2008). We want to comprehend whether the model simulations of water vapor, in their current quality, can be used to even out the deficits of the measurement-based estimates, particularly in regions with no measurements.…”
Section: Introductionmentioning
confidence: 99%